Genera Mixta in Herbert George Wells’s Industrial Romance ‘The Cone’ (1895): Realism, the Uncanny Fantastic, the Industrial Sublime and the Tragic - Françoise Dupeyron-Lafay (Cahiers Victoriens et Edouardiens)
Despite their growing importance in Victorian society, machines are underrepresented in ‘industrial’ or ‘social problem’ fiction. H. G. Wells’s short stories and novellas of the 1890s are a notable exception. While ‘The Cone’ is indebted to the mid-Victorian (cautionary) tradition and especially to Dickens’s Hard Times, these features are inflected in an innovative and pioneering way mainly due to the text’s unprecedented generic hybridity. The industrial sublime coexists with a generalized sense of melancholy, shown as the new social disease affecting middle-class characters—and no longer the working-class underdogs or ‘Hands’ of previous texts—in a disfigured world deserted by God. ‘The Cone’ could be called an ‘industrial romance’, a category subsuming its genera mixta status: its convincing, realistic substratum (the industrial world of the 1890s in the Newcastle area), its love (and revenge) plot within an industrial context, the presence of dark Biblical symbolism within the realistic mode, and an approach to the human psyche inspired from contemporary psychological research and formulated through the uncanny. The realistic descriptive regime is inflected by a fantastic form of poetics fostered by complex images of repression and voracious orality whereby the figurations of the industrial setting and its omnipresent machinery serve as indirect psychological expressions, both of the unknown depths of an individual’s psyche (Horrocks’s) and of a large-scale collective crisis, so that machinery also turns out to be the tragic paradigm of late Victorian industrial society.